Effect of Plant Density and Spatial Arrangement on Growth, Quality and Yield of Morphologically Varying Cotton Varieties - A. Babiker, Elfadil (Gezira Journal of Agricultural Science, 2021)
Field experiments were conducted at Rahad Research Station for two seasons (2000/2001 and 2001/2002) focusing on how the vari- ation in genotypes, plant density and spatial arrangement affects cotton yield and quality . The combined analysis indicated significant responses due to main effects but their interactions were not. Regr- ession analysis for plant density-yield response curve exhibited a curvilinear relationship with the highest seed cotton yield (3895 kg/ha(. achieved at 125000 plants/ha and thereafter started to decrease. Such an optimum density was achieved by planting 3 plants/hill spaced at 30cm intra-row spacing. On average, Acala (93)H out-yielded Barac (67)B and Sudac-K by 22% and 59%, respectively. Sticky cotton due to honeydew secretions was thermodetectly measured, with sticky spots for Acala 93H, Barac(67)B and Sudac-K being in the ranges of 6-40, 4-22  and 0-12, respectively. Yet ,for each variety, the sticky spots range increased concomitantly with the increase in planting density. This was discussed in relation to variability in variety specific traits such as hairiness, glabrousness and plant canopy architecture. Nevertheless, these values were dramatically lower than those recorded internationally for the Sudan Cotton. Days to the last pick were 130, 170 and 185 for Sudac-K, and Acala (93)H, respectively. Accordingly, Sudac-K which is an early maturing, super- okra-leaf (SOL), highly resistant to whiteflies( Bemisia tabaci ) but of comparatively low yield, emerged as a suitable choice for a short duration low management system where problems of late irrigation and build up of whiteflies are anticipated. Conversely, Acala (93)H (Nour 93), being hairy, physiologically efficient in compensating for yield losses due to late adversities and with stay green character is best fitted into long season high management strategy.